Comparing the Effectiveness of Assertiveness Training and Self-Regulation Intervention on Academic Self-efficacy in Female High School Students - Seyyedeh Zahra Mousavi; SoltanAli Kazemi; Mohammad Khayyer; Hosein Bagholi (Iranian Evolutionary Educational Psychology Journal, 2025)
Objective: The objective of this investigation was to evaluate the comparative efficacy of assertiveness training and self-regulation intervention on the academic self-efficacy of female high school students situated in Kouhchenar (Iran). Methods: The methodological approach employed was quasi-experimental, characterized by a pre-test, post-test, and follow-up test design, inclusive of a control group. The participant cohort for the study comprised 90 female volunteer students drawn from three classes within the first level secondary school in 2021. Participants were randomly assigned to self-regulatory, assertiveness, and control groups. Students in experimental groups were subjected to training sessions pertinent to their respective group designations for a total of 8 sessions, while the control group adhered to their standard class curricula. For the assessment at pre-test, post-test, and follow-up test (administered one month later), the Self-Efficacy Scale (Midgley et al., 1998) was utilized. The data were scrutinized utilizing repeated measures analysis (α = 0.05). Results: According to results, no statistically significant discrepancy was observed in the mean self-efficacy scores during the pre-test between the experimental and control groups; however, the post-test and follow-up test results indicated a significant difference (p < 0.05) in favor of the experimental groups compared to the control group. Furthermore, a comparative analysis revealed that the effectiveness of self-regulatory training surpassed that of assertiveness training regarding academic self-efficacy, with a pronounced difference (p < 0.001). Conclusions: In light of the findings, it can be concluded that both assertiveness and self-regulation training yield a beneficial impact on students' self-efficacy.